Potential of ornamental fish businesses on consumer tastes (case study in pohgading village, peringgabaya district, east lombok district) - Arsonariya, Arsonariya; Baiq Elbadriati (SEAN Institute, 2024)
This research is about the potential of the ornamental fish business on consumer tastes in Pohgading Village, Pringgabaya District. The aim of this research is to describe the potential of the fish business on consumer tastes in Pohgading Village, both in terms of the types of ornamental fish marketed, the marketing system and also the profits obtained. The method used is a qualitative approach, there are nine informants who are used as references in collecting information, (1). Ornamental fish business owner, (2). Pohgading Village Head, (3). People who have been involved in the ornamental fish business, (4). Society, (5). Ornamental Fish Trader, (6) Ornamental Fish Trader, (7). Ornamental Fish Trader, (8). The researcher himself has been involved in the ornamental fish business. The research results show that the ornamental fish business in Pohgading Village has the potential to influence consumer tastes, the community as consumers welcomes them in a friendly manner and has an interest in ornamental fish starting from their various shapes and colors, supported by a large ornamental fish market and suitable geographic location, The pH of the water is right for the ornamental fish business and also a strategic marketing location, this has resulted in many retail traders appearing. However, the ornamental fish business encountered major obstacles during the Covid-19 pandemic. In minimizing and preventing this outbreak, the government issued policies to be adhered to by all Indonesian citizens, so that during the new normal period, several ornamental fish traders had gone out of business and there were some who were still surviving. and get up again.